Source of introduced populations of Hemidactylus mabouia (Moreau de Jonnès, 1818) into the Eastern Cape Province and the potential spread to other South African regions - Jeme, Alungile (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Human movements globally have resulted in dispersal and introduction of terrestrial and marine organisms into areas outside of their native range. Species that have been introduced to new habitats can either be alien (not causing any harm to the new environment) or invasive alien species (destroying or competing with the indigenous species for resources). Investigating the source of these introductions is important as it provides baseline information about their biology and evolution. It also allows for better prevention measures for future invasions and for effective conservation strategies. In this study, I investigate the source of the introduced populations of tropical house geckos Hemidactylus mabouia in the Eastern Cape Province using two mitochondrial gene regions, ribosomal 16S and NADH dehydrogenase subunit 4 (ND4). We also look at the potential spread of these species using species distribution models (SDMs). The phylogeny showed that the introduced populations into the Eastern Cape were genetically similar to both H. mabouia lineages found in Central & Southern Africa. The phylogeny produced two clades from which the majority of the introduced samples were grouped in a clade with samples from Angola, DRC, and Mozambique, and only a few nested within the second clade with the South African native population. Haplotype networks from both genes also showed two clades, matching those found in the phylogeny. The introduced samples were associated with samples from Angola and those from South Africa (native) as these localities had a number of shared haplotypes. SDMs showed less evidence that these individuals could naturally move west down the coast as the probability of occurrence was below 0.4 from the Eastern Cape to the Western Cape. Our conclusion was that the introductions may be due to multiple avenues like species moving down the east coast or human translocation including trade routes. From this we can conclude that geckos are largely translocated through human movement as they are known for their opportunistic behaviours as they are commensal with humans.
Keywords: Introduced vertebrates; Hemidactylus; Tropical house gecko; Species Distribution Model; Biogeography -- South Africa -- Eastern Cape; Biological invasions